Modelamiento Cinemático Aproximado de un Prototipo de Robot Equino de 6 Grados de Libertad Para un Simulador de Tiro - Ramírez, Jaime Eduardo Andrade; Rubio, Yeison Andrey Gómez; Rivera, Diego Andrés Carranza (KnE Engineering, 2018)
This article shows the design, analysis and manufacturing of one equine robot prototype with six degrees of freedom along with the development and implementation of control software. This software has the purpose to drive and to calculate the robot kinematics. All of this allows studding the elements necessaries to make a simulator of shots for riders that can be used in education areas as a tool of didactic support in the courses in the police national of Colombia, ensuring that the riders do not suffer physical and psychological injuries during their formation and avoiding hurting the horses in the training of that courses. In addition, the riders can interact and experiment of safety way every situation that they could find in real practice. The system is based on the kinematic study according to the Denavit-Hartenberg algorithm, approximate simulation using Kinematic-ARM® and the mathematic medeling in the Matlab® programming environment. All tecniques give aproximate results of location of the manipulator tool. Finally, it is possible to validate and analising the results comparing the practical and theoric values to determine the TCP error estimated in each movement. Keywords: Direct kinematics, equine robot, Denavit-Hartenberg (D-H), Degrees of Freedom (DOF), Tool Center Point (TCP).